Gene deletion studies in analysis of the role of cytochrome P450 in flaviolin metabolism in Streptomyces coelicolor. - Lara Martin Sanchez (2009)
"Cytochromes P450 monooxygenases play important roles on oxidative decoration of secondary metabolites in Streptomycetes. Cytochrome P450 158A2 (CYP158A2) and CYP158A1 of Streptomyces coelicolor A3(2) are two of the 18 CYPs that comprise the CYP complement or "CYPome" of S. coelicolor A3(2). CYP158A2 catalyzes an unusual oxidative C-C coupling reaction to polymerize flaviolin (a red pigment) into three isomers of biflaviolin and one triflaviolin which are pigments responsible for UV radiation protection in Streptomyces. Although located in a different part of the chromosome, CYP158A1, sharing 61% aminoacid identity with C\T158A2, has also been shown to produce almost identical flaviolin-derived products. The gene scol207 encoding for CYP158A2 was previously deleted and this mutant showed no changes on phenotype with respect to the wild type. Given that the production of the same flaviolin-derived compounds can be achieved as well by CYP158A1, this CYP is thought to be the substitute for CYP158A2 in the biosynthesis of those pigments, enforcing the mechanism for UV protection in these organisms. In order to investigate functional redundancy between CYP158A1 and CYP158A2, PCR-based targeted mutagenesis was carried out to delete the gene sco6998 encoding for CYP158A1 in a wild type strain (to create a single mutant) and in a strain with the gene for CYP158A2 already deleted (to create a double mutant for both genes). Phenotype observation of the mutants and metabolomic studies by mass spectrometry analyses were carried out in order to identify and quantify the amount of flaviolin in every mutant compared to the parental strain. Furthermore UV sensitivity assays were performed to measure the effect of the lack of those pigments. The results obtained will shed light in the understanding of the function of such valuable and diverse proteins as are the CYPs, and highlight the importance of this pathway in the production of novel secondary metabolites with important biological activities."